Performance evaluation of bio/chemical leaching solution and nano catalyst in upgrading and enhancing oil recovery - Mohammad Hossein Shabani; Parya Torkaman; Hamidreza Farshadfar; Arezou Jafari; Seyyed Mohammad Mousavi (Results in Engineering)
Heavy oil high viscosity poses significant challenges for recovery, with thermal methods often incurring high economic and environmental costs. Metal catalysts are known for their efficiency and effectiveness in oil upgrading processes. This research is novel as it emphasizes the utility of solid waste in catalyst preparation and introduces a groundbreaking comparative analysis of catalysts produced through both chemical and biological leaching methods, highlighting their environmental benefits and efficacy in improving oil recovery. We investigated the effects of various parameters influencing this process, including catalyst type, concentration, and reaction temperature, using design of experiments methodologies. The recovery of metal from electric arc furnace dust during chemical leaching was 15.1 %, while it was only 3.2 % in biological leaching. Additionally, the viscosity of the oil decreased by 10.2 %, 12.5 %, and 22 % with the addition of the bioleaching solution (conc: 0.01 wt.%, T: 50 °C), electric arc furnace dust (conc: 0.1 wt.%, T: 70 °C), and Fe3O4 (conc: 0.1 wt.%, T: 70 °C) nanoparticles, respectively. The reason for this is the catalytic activity of these metals, which facilitates the breakdown of heavy molecules and enhances the quality of crude oil. Notably, the enhancement in oil recovery after the upgrading process with the injection solution containing nano Fe3O4 and the biological catalyst was 61 % and 41 %, respectively. The comprehensive evaluation of catalytic performance under dynamic conditions provides valuable insights into optimizing recovery processes and underscores the dual economic and environmental benefits of this approach.